Diffuse Peritonitis due to Perforated Gastric Ectopic Pancreas - Nobutada Fukino; Takatsugu Oida; Kenji Mimatsu; Kazutoshi Kida; Atsushi Kawasaki; Youichi Kuboi; Hisao Kano (Case Reports in Gastroenterology, 2012)
Ectopic pancreas is frequently found in the gastrointestinal tract. Lesions comprise well-developed and normally organized pancreatic tissue outside the pancreas, without anatomic or vascular connections with the true pancreas. Most patients with ectopic pancreas are asymptomatic or exhibit nonspecific symptoms. A 68-year-old Japanese woman had been experiencing intermittent pain in the right upper abdomen. Suddenly, the abdominal pain changed to intense pain in the right flank of the abdomen 2 days later. On initial medical examination, the abdomen exhibited rebound tenderness and distension. The results of laboratory tests revealed increased inflammatory reaction. Abdominal computed tomography showed free air and ascites on the surface of the liver and elevated levels of adipose tissue around the antrum and pylorus of the stomach. Perforation of the upper gastrointestinal tract was diagnosed and we performed urgent surgery. The site of perforation, whose size was 25 mm, was the lesser curvature of the antrum of the stomach. Since it was not possible to perform omentopexy, we performed extensive gastric resection. The reconstruction was a Billroth II operation. Microscopic analysis revealed pancreatic tissue within the ulceration, showing islets of Langerhans, acini, and ducts; the lesion was diagnosed as type I using Heinrich’s criteria. The postoperative course was uneventful. The patient was discharged on day 13 and remains clinically healthy. Gastric perforation due to ectopic pancreas has been reported in 2 cases, including our patient, and is extremely rare. Once gastric perforation has been diagnosed, the presence of ectopic pancreas might be considered.